2006
DOI: 10.1021/pr060181p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Outer Membrane Protein Profile from Disease-Related Helicobacter pylori Isolates by Subcellular Fractionation and Nano-LC FT-ICR MS Analysis

Abstract: Because of the important role of membrane proteins in adhesion, invasion, and intracellular survival of pathogens in the host, membrane proteins are of potential interest in the search for drug targets or biomarkers. We have established a mass spectrometry-based method that allows characterization of the outer membrane protein (OMP) profile of clinical isolates from of the human gastric pathogen Helicobacter pylori. Subcellular fractionation and one-dimensional gel electrophoresis (1D-GE) analysis was combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…The HP0025 gene, which encodes an outer membrane protein (Omp2), was identified among the genes that were present less frequently in DU isolates. In accordance with our results, a recent report found that the protein was less frequently expressed in isolates from DU cases (10). In contrast, it is noteworthy that this gene was present in 100% of the GC isolates.…”
Section: Vol 77 2009 Novel Cancer-associated H Pylori Genes 2207supporting
confidence: 93%
“…The HP0025 gene, which encodes an outer membrane protein (Omp2), was identified among the genes that were present less frequently in DU isolates. In accordance with our results, a recent report found that the protein was less frequently expressed in isolates from DU cases (10). In contrast, it is noteworthy that this gene was present in 100% of the GC isolates.…”
Section: Vol 77 2009 Novel Cancer-associated H Pylori Genes 2207supporting
confidence: 93%
“…The method for in-gel protein digestion with trypsin described by Shevchenko et al (35) was applied with some minor modifications (34). Briefly, the gel pieces were destained by washing three times in 25 mM NH 4 HCO 3 in 50% CH 3 CN and one time in 25 mM NH 4 HCO 3 in 50% CH 3 OH.…”
Section: Glycan Analysis Of Fel D 1 Using In-gel Protein Digestion Anmentioning
confidence: 99%
“…The protein compositions of EPIMs (Blomqvist et al 2006) and whole etioplasts Kleffmann et al 2007) have been analysed, though no previous study has focused on the PLB proteome. We adopted a relatively new combination of analytical methods, with high potential in proteomic analysis-the one-dimensional (1-D) sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) combined with nanoliquid chromatography Fourier transform-ion cyclotron resonance mass spectrometry (nano-LC FTICR MS), an approach used with great success (Olsen et al 2004;Carlsohn et al 2006). By this method, proteins are separated by SDS-PAGE, and gel pieces from an entire sample lane are excised and subjected to mass spectrometry analysis.…”
Section: Introductionmentioning
confidence: 99%